A rapid colloidal gold immunochromatographic assay based on polyclonal antibodies against HtpsC protein for the detection of Streptococcus suis - Lu, Yawei; Wang, Sibo; Cai, Xushen; Cao, Min; Lu, Qingyu; Hu, Dan; Chen, Qiong; Xiong, Xiaohui (Frontiers in Microbiology, 2023)
An efficient and rapid immunochromatographic assay (ICA) has been engineered for the detection of Streptococcus suis (S. suis). The underpinning principle of this ICA test lies in the use of polyclonal antibodies (pAbs) decorated with colloidal gold, which are specific to S. suis.These pAbs were derived from rabbits immunized with type II histidine triad protein (HtpsC) and HtpsC-N of S. suis. The sensitivity of the ICA was noteworthy, identifying S. suis at bacterial concentrations as diminutive as 1.0×10 3 CFU/mL. Moreover, the assay demonstrated respectable specificity and did not indicate false positives for other bacterial species (Escherichia coli, Salmonella, Staphylococcus aureus, Listeria monocytogenes, Streptococcus pyogenes, Streptococcus lactis, or Enterococcus faecalis). The assay was also capable of detecting multiple S. suis serotypes containing the htpsC gene, including serotypes 1-9, 12, 14, 16 and 23. Nonetheless, the detection of S. suis that lacks the htpsC gene remained beyond the capabilities of this assay. A simultaneous analysis of 16 samples utilizing PCR substantiated the reliability of the ICA test. The assay's results can be procured within a 15-minute window, making it a suitable option for field application. Broadly, this study underscores the potential of the HtpsC protein as a target antigen for the detection of S. suis, and proposes that the HtpsC protein be evaluated further in other detection assays specific for S. suis.